THE USE OF TEXT-BASED APPROACH TO ENHANCE STUDENTS’ ABILITY IN ANALYZING DISCOURSE: A REFLECTIVE PAPER - Mohammad Abraham Akbar Eisenring (Fakultas Bahasa dan Seni UNP, 2019)
AbstractA great number of teachers apply various approaches in the way they teach discourse analysis. One of those are known as text-based approach, which allows the learners to explore and interact with the texts in purpose to acquire comprehensive understanding about the texts. In this paper, the writer attempts to review some literatures dealing with text-based approach as well as to qualitatively report the reflection of teaching practice done by the writer in the field of discourse analysis by using text-based approach. This present study belongs to descriptive qualitative study. The participants of the study were six master students who study in different universities in Yogyakarta. The result of the study showed that use of text-based approach, presumably, was able to improve the learners’ ability in analyzing discourse. Keywords: Text-Based Approach, Discourse Analysis, Teaching Reflection, English Language Teaching and Learning. AbstrakBanyak guru-guru menerapkan berbagai macam pendekatan di dalam pengajaran analisis wacana mereka. Satu di antaranya dikenal sebagai pendekatan berbasis teks, yang memungkinkan siswa untuk bereksplorasi dan berinteraksi dengan teks dengan tujuan untuk memperoleh pemahaman yang luas terkait dengan teks tersebut. Di dalam artikel ini, penulis mencoba untuk mengulas beberapa literatur-literatur yang terkait dengan pendekatan berbasis teks dan juga melaporkan secara kualitatif refleksi hasil praktek mengajar yang dilakukan oleh penulis dalam ruang lingkup analisis wacana dengan menggunakan pendekatan berbasis teks. Studi dewasa ini tergolong ke dalam studi deskriptif kualitatif. Peserta studi ini adalah enam mahasiswa magister yang berkuliah di universitas yang berbeda di Yogyakarta. Hasil dari studi ini menunjukkan bahwa penggunaan pendekatan berbasis teks, kiranya, mampu untuk meningkatkan kemampuan siswa dalam menganalisis wacana.Kata kunci: Pendekatan Berbasis Teks, Analisis Wacana, Refleksi Pengajaran, Pengajaran dan Pembelajaran Bahasa Inggris.